(untitled) (Damascus University Journal of agriculture sciences, 2026)
Abstract The research was conducted at Biotechnology Lab, Faculty of Agriculture – Damascus University/ Syria, during the season2021 /2022. Seeds of 12 genotypes were germinated after collecting from ecologically dissimilar syrian provinces, (two wild barley types and cultivated or proved type from each province) to determine the genetic relationship by using ISSR technique (Inter Simple Sequence Repeats) with 14 primers. The analysis results revealed that 13 primers showed polymorphism among the evaluated genotypes, primers gave a total of 61 pigments with a polymorphic percentage of %91.66, the average of Polymorphic information content (PIC) ranged between 0.181 as a lowest value and 0.352 as a highest value . Varieties dendrogram separated into two major clusters, the first cluster included the cultivated and all wild genotypes of a type H.spontaneum with different degrees of genetic relationship, as Arabi Abiad and Ararbi Aswad were genetically the closest with a gentic distance 1.539. While the second cluster contained all wild genotype which kind H.marinum, as the models H.marinum(Daraa) and H.marinum (AL-swidaa) were genetically the closest with a gentic distance 3.126.